2014
DOI: 10.1016/j.jcot.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Patellar clunk in total knee arthroplasty using modified Sigma posterior stabilized femoral component

Abstract: Removal of the sharp ridge in the intercondylar groove in the newer implant seems to have been effective in reducing the incidence of the patellar clunk. It also indicates that the sharp ridge was the most probable cause of the clunk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Numerous numbers of studies on patellofemoral or femorotibial joint problems have been published in the literature. 2 , 3 , 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 However, the focus of the present case was on the post-cam function. To our knowledge, only a few cases of post-cam dysfunction have been reported.…”
Section: Discussionmentioning
confidence: 80%
“…Numerous numbers of studies on patellofemoral or femorotibial joint problems have been published in the literature. 2 , 3 , 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 However, the focus of the present case was on the post-cam function. To our knowledge, only a few cases of post-cam dysfunction have been reported.…”
Section: Discussionmentioning
confidence: 80%
“…Within their study, however, the patella was not resurfaced, making comparisons with this current study unreliable. More recently Rajshekhar et al 19 evaluated the HP Sigma Press Fit Condylar component (group B) in a noncomparative study and identified an incidence of 2% patellar clunk. Their study is more limited than the current study because it includes only 133 patients who all received the HP Sigma Press Fit Condylar component and bearing choice was not identified.…”
Section: Discussionmentioning
confidence: 99%